2022
DOI: 10.7146/qhc.v1i1.127258
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing COVID-19 public health communication for culturally and linguistically diverse communities: An Australian interview study with community representatives

Abstract: Background: Public health crises present challenges for providing accessible, timely, and accurate health information to culturally and linguistically diverse (CALD) communities. Aim: The aim of this qualitative project was to explore strategies used by CALD community organizations to improve communication about COVID-19 for their communities; we also aimed to identify gaps and challenges. Methods: We interviewed 16 representatives from Greek, Italian, and Chinese CALD organizations in Melbourne, Australia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Chatbots are especially useful in this context as they are capable of reaching key vulnerable demographics. Public health recommendations are often perceived as unclear by young people, migrants and refugees in nations around the world (Ahmed, 2018;Karidakis et al, 2022). It is more common for such marginalised groups to attain information on COVID-19 through social media.…”
Section: Use Case: Public Health Communicationmentioning
confidence: 99%
“…Chatbots are especially useful in this context as they are capable of reaching key vulnerable demographics. Public health recommendations are often perceived as unclear by young people, migrants and refugees in nations around the world (Ahmed, 2018;Karidakis et al, 2022). It is more common for such marginalised groups to attain information on COVID-19 through social media.…”
Section: Use Case: Public Health Communicationmentioning
confidence: 99%
“…When asked why the elderly couple could not obtain information through regular information channels, one social worker said, 'I don't think they have any information sources at all. They had no idea what was going on' (see a detailed analysis of this and similar cases in Karidakis et al 2022).…”
Section: Electronic Messagingmentioning
confidence: 99%
“…Despite the clear need for improved communication on COVID-19 to CALD populations, there is a relative dearth of literature on the subject. One qualitative Australian study conducted in 2020 found that CALD community organisations were effective intermediaries for public health communication, however this research was conducted with three large, well-established CALD groups in Melbourne (Chinese, Italian and Greek) [ 16 ]. The authors highlighted the need for future studies to focus on recent arrivals, including refugee communities [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One qualitative Australian study conducted in 2020 found that CALD community organisations were effective intermediaries for public health communication, however this research was conducted with three large, well-established CALD groups in Melbourne (Chinese, Italian and Greek) [ 16 ]. The authors highlighted the need for future studies to focus on recent arrivals, including refugee communities [ 16 ]. Another Australian study conducted during the pandemic utilised a participatory approach to understand the role of CALD community leaders in communicating health information, however study participants were limited to community leaders, advocates and bi-cultural workers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%